Synthesis of a Tin(II) 1,3-benzobis(thiophosphinoyl)methanediide complex and its reactions with aluminum compounds - Yang, Yi-Fan (2013)
The synthesis of a tin(II) 1,3-benzobis(thiophosphinoyl)methanediide complex and its reactions with aluminum compounds are reported. The reaction of the 1,3-benzodiphosphole disulfide [1,3-C6H4(PhP═S)2CH2] (4) with [Sn{N(SiMe3)2}2] in refluxing toluene afforded the tin(II) 1,3-benzobis(thiophosphinoyl)methanediide [{μ-1,3-C6H4(PhP═S)2C}Sn]2 (5). The X-ray crystal structure of 5 shows that it has a 1,3-dimetallacyclobutane structure. The reaction of 5 with 1 equiv of AlCl3 in CH2Cl2 afforded [1,3-C6H4(PhP═S)2C(Sn){Sn(S═PPh)2C(AlCl3)-1,3-C6H4}] (6). The reaction proceeds via an insertion of a AlCl3 molecule into one of the Sn–C bonds in 5. The reaction of 5 with 2 equiv of AlCl3 in CH2Cl2 afforded [1,3-C6H4(PhP═S)2C(Sn)(AlCl3)] (7). The reaction appears to proceed via the formation of compound 6, which then undergoes an insertion with another AlCl3 molecule to form compound 7. The transmetalation reaction of 5 with 2 equiv of AlMe3 in CH2Cl2 afforded [1,3-C6H4(PhP═S)2CAlMe]2 (8), which contains a terminal Cmethanediide–Al bond.